2021
DOI: 10.1155/2021/3628481
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics of Inpatients Undergoing Surgery for Glaucoma at Tianjin Eye Hospital from 2013 to 2017

Abstract: Purpose. To analyze the epidemiological characteristics of inpatients who underwent surgery for glaucoma at Tianjin Eye Hospital from 2013 to 2017. Methods. All glaucoma inpatients who underwent surgery at Tianjin Eye Hospital from 2013 to 2017 were evaluated. The relationships of age and sex with different types of glaucoma were analyzed. The differences in the prevalence and family history of glaucoma among patients with different systemic diseases were compared. Additionally, the effects of different surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…PACG is more common in Asians than in Africans or Europeans [34] . This study showed that angle-closure glaucoma and secondary glaucoma were the most common types of glaucoma cases at the Eye Hospital of Wenzhou Medical University, which matched the findings of studies conducted in Shanghai [35] , Tianjin [36] , and Beijing [37] . In regard to angleclosure glaucoma, the proportion of internal filtration surgeries increased slightly from 2015 to 2021 to over 70% of patients.…”
Section: Trend Of Glaucoma Internal Filtration Surgeriessupporting
confidence: 83%
“…PACG is more common in Asians than in Africans or Europeans [34] . This study showed that angle-closure glaucoma and secondary glaucoma were the most common types of glaucoma cases at the Eye Hospital of Wenzhou Medical University, which matched the findings of studies conducted in Shanghai [35] , Tianjin [36] , and Beijing [37] . In regard to angleclosure glaucoma, the proportion of internal filtration surgeries increased slightly from 2015 to 2021 to over 70% of patients.…”
Section: Trend Of Glaucoma Internal Filtration Surgeriessupporting
confidence: 83%
“…Age and glaucoma types differed between both sexes; the most remarkable difference was the much higher rate of the PACD in women than men; these correspond well with the previous reports that the older age and female gender were risk factors for PACD. 12 , 13 Difference in glaucoma types also explains well with the higher rate of patients who were treated with cataract extraction + goniosynechialysis in female group.…”
Section: Discussionmentioning
confidence: 78%
“…The primary universal cause of persistent blindness is glaucoma (Stein et al, 2021). By 2040, there will likely be 111.8 million glaucoma patients between the ages of 40 and 80 years (Yang et al, 2021). Age, smoking status, African heritage, family history, genetics, hypertension, hypotension (especially lowered nocturnal blood pressure), atherosclerosis, lipid dysregulation, and diabetes are all risk factors for developing glaucoma (Schuster et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…When glaucoma was divided into stages based on severity, the proportion of patients with early stage glaucoma was greater than that of those with middle and late stage glaucoma and there were more patients without diabetes or hypertension at each stage of glaucoma. Diabetes is linked to microvascular damage and possibly impacts the vascular autoregulation of the retina and optic nerve (Yang et al, 2021). One study found that those with diabetes had a higher risk of increasing glaucoma than people without diabetes, but another found no correlation between the prevalence of glaucoma and diabetes (Rim et al, 2018;Grzybowski et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation